ANALYSIS OF THE CURRENT SITUATION OF INNOVATIVE ENTREPRENEURSHIP IN THE DIGITALIZATION PROCESS OF UKRAINE’S ECONOMY - Gura, V.; Skopenko, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article considers the issue of digitalization of the innovation sphere of Ukraine. The urgency of the issue of development of innovative entrepreneurship with the use of new technologies, developments and approaches for the successful positioning of the country in the international arena, as well as the opening of new opportunities and prospects. The main problems in the country’s innovation activity are highlighted: the lack of a clearly formulated strategy by the government for innovative development, outdated material and technical base, lack of financial resources. The initiatives of the government that are the impetus for the development of the country are emphasized: "State in the smartphone" – the application "Diia", the functionality of which is a considerable list of services; "Available Loans 5-7-9%" – the longest loan can be granted for 5 years, and the largest amount reaches up to UAH 3 million; which allow the development of innovative entrepreneurship without obstacles. Three main ratings on the level of innovation of Ukraine are analyzed: Global Innovation Index, Bloomberg Innovation Index and IMD World Competitiveness ranking. Ukraine’s position in these rankings remains quite low and our country is still far from the leaders - Switzerland, Britain, Sweden, the Netherlands and the United States, which indicates the need for a new approach to competition and changes in public policy on this issue, because innovation is the key to long-term economic growth. Ways to improve and stimulate the development of Ukraine’s innovation sphere are considered: to unite the efforts of governmental, scientific and business circles of society to comprehensively address strategic and tactical issues of national innovation in the context of globalization challenges, which allows to ensure our country’s competitiveness. Creating such a coherent system requires: reducing the tax burden on innovative companies, the development of international scientific and technical relations through the exchange and use of new knowledge and technologies, increasing the effectiveness of government programs in the financing system.